Analisis Kinerja Keuangan pada PT. Gudang Garam Tbk yang Terdaftar di Bursa Efek Indonesia Periode 2012-2021 - Maria Martha; Andreas Rengga; Margaretha Yulianti (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
This research aims to assess the financial performance of PT. Gudang Garam Tbk by using financial ratio analysis. The population of this study is the financial statements of PT. Gudang Garam Tbk for the years 2012 to 2021, while the sample is the balance sheet and profit and loss report for the 2012-2021 period. Data was collected using documentation techniques, and analyzed using financial ratio analysis, namely liquidity ratios (CR, QR, CAR), solvency ratio (DAR, DER), profitability ratios (NPM, ROA,ROE), and activity ratios (RTO, TATO). Findings of the study indicated that PT. Gudang Garam Tbk’s financial performance was generally poor. This is examined: 1). Each indicator’s findings are show in the liquidity ratio; the current ratio falls into the “good” category, while the quick ratio and the cash ratio fall into the “bad” category. 2). The ratio of assets to debt and the equity to debt are in the unfavorable group, according to the solvance ratio, which displays the outcomes of each indicator. 3). The profitability ratio displays the outcomes of each adverse indicator, including the net profit margin ratio, return on assets ratio, and return on equity ratio. 4). The acivity ratio show the results of each indicator, the accounts receivable turnover ratio is in the good category and the assets turnover ratio is in the bad category.